PENILAIAN CARA MENGAJAR MENGGUNAKAN RANCANGAN ACAK LENGKAP (Studi kasus: Cara Mengajar Dosen Jurusan Statistika UNDIP) - Muhammad, Ilham; Rusgiyono, Agus; Mukid, Moch. Abdul (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
Completely randomized design (CRD) is the simplest design among the designs of other experiments. In this treatment plan is fully charged randomized trial units or vice versa. Do research to find out how to rank professors teach statistics Diponegoro University Diponegoro University by alumnus statistics. This study used a RAL because only treatment variable that will be compared. Alumni variables as replication and assumed homogeneous. From the analysis of variance for the CRD, it is concluded that faculty groups differed significantly was A, P, O and L